Homogenization of elastic plate equation∗ - Burazin, Krešimir; Jankov, Jelena; Vrdoljak, Marko (Mathematical Modelling and Analysis, 2018)
We are interested in general homogenization theory for fourth-order elliptic equation describing the Kirchhoﬀ model for pure bending of a thin solid symmetric plate under a transverse load. Such theory is well-developed for second-order elliptic problems, while some results for general elliptic equations were established by Zhikov, Kozlov, Oleinik and Ngoan (1979). We push forward an approach of Antoni´c and Balenovi´c (1999, 2000) by proving a number of properties of H-convergence for stationary plate equation.